Ekonomi Islam: Solusi terhadap Berbagai Permasalahan Sosial-Ekonomi - Syaparuddin, Syaparuddin (STAIN Salatiga, 2010)
The goal of this article is to find some solutions to recover sosial-economicproblems. Its focusing on Islamic economc concept. The history showed that theIslamic economic system was very effective to recover many kinds of socialeconomicproblems, because it was implemented according to Alquran andHadith. It means that if Islamic economy is implemented well and truely, manycrucial social-economic problems can be anticipated. In short, Islamic economycan be made as a means to increase societys welfare. so that any social-economicproblems wont apprear if Islamic economy is implemented well and truely.Keywords: Social-economic problems, Islamic Economic, solutions